The Quality of the Footwear that Appears on the European Single Market in the Context of Its Effect on Consumer Health and Safety. Part 2 - Elżbieta BIELAK (Communications of International Proceedings, 2021)
The article presents a continuation of the analysis of the data from the Rapid Alert System for Dangerous Non-Food Products (RAPEX) for footwear notified in this system in the years 2004-2020. Such risks as choking, injuries/ injury, fire, environment and other hazards posed by footwear to consumers, next to chemical one discussed in the first part of article, are described. The actions undertaken by public authorities and economic operators due to appearance and identification of unsafe footwear in European markets are indicated. Attention is paid to countries from which most often come products notified to the RAPEX, and countries showing the highest activity in notifying. Based on data analysis it has been found that risks mentioned above in most cases refer to children's shoes and among other things, are associated with failure to meet requirements laid down in relevant standards. Children's shoes pose a threat to young consumers due to a risk of choking and suffocation by small elements improperly attached to shoes. Sporadic cases of notifications apply to possibility of injury, stumbling and slipping, improper design, lack of instructions for use in proper language, as well the risk of fire or environment risk. Unsafe footwear is produced mainly in China, and notified to the RAPEX by Spain.
Keywords: Child safety; Footwear quality; RAPEX; Choking; Injures.